Time and time again: the reincarnations of coerced sterilisation - Fofana, Mariam O. (Journal of medical ethics, 2022)
The recently reported cases of coerced sterilisation of women at a privately operated immigration detention facility in the USA are egregious in their disregard for human dignity and professional ethics, but sadly not surprising. These abuses represent a continuation of efforts to control the reproductive capacity of women, fueled by racist and xenophobic motives. Physicians helped create and legitimise the pseudoscientific framework for the eugenics movement, which would implement forceful sterilisation as its tool of choice to eliminate undesirable traits that were thought to be biologically inherited and predominant among racial and ethnic minorities. Although state-endorsed forcible sterilisation programs have ended, incarcerated women have remained particularly vulnerable to sterilisation abuse. The intersectional vulnerabilities of racism, xenophobia and carcerality must be addressed to prevent such abuses from recurring.